Multivariate analysis of chemical attributes of an oxisoil under Saccharum spp. and Pinus spp., Batatais, São Paulo - Marcelo Zanata (Scientific Electronic Archives, 2021)
This study aims investigate the correlations of soil chemical attributes in watersheds in order to highlight the changes caused by soil management, differentiating them by multivariate statistical analysis. The watersheds of the first order of magnitude were selected three occupied with sugarcane, three with the Pinus reforestation and a witness with greater occupation of native forest. The composite samples of soil were collected at five points around each major source in depth 0-0,2 m, on two occasions (April and December). The first two factors aggregated 58.09% of the total variance of the initial data (F1 = 44.80%; F2 = 13.29%). The first factor shows a direct correlation between the pH, Ca, Mg, SB and V variables, which are inversely correlation with H+Al and Al variables, showing the process of soil acidity correction (lime) in the occupied watersheds with sugarcane crop. The second factor show a direct correlation between the T, OM and Cu variables, indicating high soil acidity in reforestation of Pinus. The multivariate analyses show the change of the agroecosystem of watersheds studied as a function of soil management.